Budget Impact Analysis of Chronic Myeloid Leukemia Treatment in Patients with Imatinib Failure from the Brazilian Public Health System Perspective: Supporting Health Care Decisions on Central and Local Levels - Moellmann-Coelho, Arthur (2010)
Introduction: In recent years, it has been increasingly recognized that a comprehensive health technology assessment should include not only a cost-effectiveness analysis, but also a budget impact analysis. Objective: A budget impact analysis was conducted to assess the costs of the treatment for patients with chronic myelogenous leukemia within a period of three years after imatinib failure from both central level (Brazilian public health system) and local level (public hospital) perspectives. Methods: A decision model based on clinical and epidemiological data was developed to compare current treatment options (dasatinib and imatinib) reimbursed by the Brazilian government with different scenarios that included nilotinib. Results: In our base case using official pharmaceutical prices, adding nilotinib to the mix of technologies is expected to increase total expenses within the next three years at the central level by up to R$11,360,282 or R$17,930 per patient per year, and at the local level by up to R$16,437 per patient per year. In the alternative case, based on prices from the latest public tenders, adding nilotinib to the mix of technologies is expected to increase total expenses within the next three years at the central level by up to R$31,692,792 or R$26,000 per patient per year, and at the local level by up to R$26,600 per patient per year. Conclusion: Results from this analysis can be used to estimate the affordability for the next three years of treatments for different chronic myelogenous leukemia phases in patients who are resistant to or intolerant of imatinib.